2017
DOI: 10.5603/arm.2017.0018
|View full text |Cite
|
Sign up to set email alerts
|

Speech Therapy—A Non-Pharmacological Method to Manage Difficult-to-treat Chronic Cough

Abstract: Cough is the most common symptom of respiratory diseases. The results of management of chronic cough in adults are still unsatisfactory. Unexplained and difficult-to-treat chronic cough causes significant impairment in patients' quality of life. The results of recent studies suggest that speech therapy (speech language intervention) is one of the few methods which are usefull in management of persistent chronic cough. We present a case of a patient with chronic cough due to chronic nonallergic rhinitis and gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Therefore it was so important for us to implement that technique and assess its efficacy in Polish population, since such a therapeutic approach had not been commonly used in Poland before. To our knowledge there has been only one case report published so far, which referred to trial of speech therapy in management of difficult-to-treat chronic cough in Poland [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it was so important for us to implement that technique and assess its efficacy in Polish population, since such a therapeutic approach had not been commonly used in Poland before. To our knowledge there has been only one case report published so far, which referred to trial of speech therapy in management of difficult-to-treat chronic cough in Poland [25].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing laryngeal stimulation can slow the speed of reaching the cough threshold, and maintaining laryngeal hydration and laryngeal massage can reduce the laryngeal hypersensitivity response, thus reducing the laryngeal muscle spasm or vocal cord abnormal movement caused by laryngeal stimulation and reducing the risk of subsequent injury. Breathing exercises are conducive to reducing adductor activity during expiration, thus reducing coughing [ 33 ].…”
Section: Possible Mechanisms Underlying Non-pharmacologic Therapymentioning
confidence: 99%
“…91 In an open study design, Ryan et al 92 identified that SPT improved cough-related quality of life and cough reflex sensitivity, which has also been evidenced by several case series that consisted of small patient populations and no control groups. 93,94 Vertigan et al 95 conducted a randomized, placebo-controlled study that enrolled 87 patients (mean age = 59.4 years, 74% female) with CRC who were randomly assigned 4 individual 30-minute intervention sessions recorded over a 60-day period (intervention) or healthy lifestyle education (placebo). The treatment group had a significant reduction in negative symptoms associated with cough (P < 0.001), breathing (P < 0.001), voice (P < 0.001), upper airway (P < 0.001), and symptom limitation on daily activities (P < 0.001) following the intervention.…”
Section: Speech Pathology Treatmentmentioning
confidence: 99%